Comparison of Imaging Modalities in the Diagnosis and Tumor Staging of Colorectal Adenocarcinoma - Serinsöz, Serdar; Aktürk, Remzi (Current Medical Imaging, 2023)
Background: Colorectal cancer is a malignancy that affects the gastrointestinal tract. Clinical diagnosis has routinely been done with colonoscopy in conjunction with digital rectal and histological examinations. Objective: We show that CT, MRI, and MRI-DWI are all effective in T-staging colorectal adenocarcinoma when compared to pathology examination. However, differences in the detection and diagnostic agreement rates between the imaging modalities for the specific T-stages were observed. Methods: Fifty-six patients diagnosed with colorectal adenocarcinoma and underwent contrastenhanced abdominal CT, non-contrast MRI, or MRI-DWI between January 2014 and March 2020 were retrospectively examined and compared to a biopsy or postoperative pathological T-stage. Results: The total diagnostic agreement rate for CT, MRI, and MRI-DWI were 58.93%, 76.79%, and 85.71%, respectively. T-staging was statistically and significantly different across all four stages analyzed for all imaging modalities. The T1-stage for MRI and MRI-DWI compared to pathology rates were statistically significant, whereas MRI-DWI and CT both demonstrated statistical significance for T3 and T2 stage comparison, respectively. Furthermore, a statistical and significant difference between the total stage comparison of MRI, MRI-DWI, and CT compared individually to pathology was also observed. All imaging modalities were able to statistically and significantly identify tumors based on tumor size according to the ROC analysis. Conclusion: These data suggest that CT, MRI, and MRI-DWI can identify and aid visually in the diagnosis of adenocarcinoma colorectal cancer. MRI-DWI is more specific and sensitive in the diagnosis and staging of colorectal tumors.
Keywords: Imaging modalities